The description of post-operative nausea and vomiting in curettage while under general anesthesia - Hani, Winarni; Burhan, Asmat; Heri Wibowo, Tophan; Suandika, Made (Global Indonesia Health Care (GOICARE), 2025)
Background General anesthesia is the process of eliminating consciousness using medications. Curettage is the procedure to remove leftover conception material from the uterus. Currently, 37.5% of curettage procedures are due to blighted ovum. The curettage procedure causes discomfort, so it needs to be assisted with anesthesia. Purpose: to determine the incidence of PONV in post-curettage patients under general anesthesia. Method Descriptive research with a cross-sectional design. The respondents were 47 women who underwent curettage due to incomplete abortion, retained placenta, and blighted ovum, selected using a purposive sampling technique. The instruments used are a demographic data questionnaire and The Rhodes Index Nausea, Vomiting and Retching (RINVR). Data analysis employs frequency distribution. Result The characteristics of the respondents are dominated by young adults (89.4%) who have experienced PONV (23.4%). Other characteristics include that all of them do not smoke and use opioids. Based on the RINVR scale, the respondents predominantly experience light PONV (46.8%). Conclusion Post-curettage patients under general anesthesia predominantly experience light PONV (Postoperative Nausea and Vomiting).